Motivators, enablers, and barriers to building allied health research capacity - Pager, Susan (Dove Medical Press, 2012)
PURPOSE: A sound, scientific base of high quality research is needed to inform service planning and decision making and enable improved policy and practice. However, some areas of health practice, particularly many of the allied health areas, are generally considered to have a low evidence base. In order to successfully build research capacity in allied health, a clearer understanding is required of what assists and encourages research as well as the barriers and challenges. PARTICIPANTS AND METHODS: This study used written surveys to collect data relating to motivators, enablers, and barriers to research capacity building. Respondents were asked to answer questions relating to them as individuals and other questions relating to their team. Allied health professionals were recruited from multidisciplinary primary health care teams in Queensland Health. Eighty-five participants from ten healthcare teams completed a written version of the research capacity and culture survey. RESULTS: The results of this study indicate that individual allied health professionals are more likely to report being motivated to do research by intrinsic factors such as a strong interest in research. Barriers they identified to research are more likely to be extrinsic factors such as workload and lack of time. Allied health professionals identified some additional factors that impact on their research capacity than those reported in the literature, such as a desire to keep at the “cutting edge” and a lack of exposure to research. Some of the factors influencing individuals to do research were different to those influencing teams. These results are discussed with reference to organizational behavior and theories of motivation. CONCLUSION: Supporting already motivated allied health professional individuals and teams to conduct research by increased skills training, infrastructure, and quarantined time is likely to produce better outcomes for research capacity building investment.